Activation of the Nlrp3 Inflammasome Contributes to Shiga Toxin-Induced Hemolytic Uremic Syndrome in a Mouse Model - Song, Liqiong; Xiao, Yuchun; Li, Xianping; Huang, Yuanming; Meng, Guangxun; Ren, Zhihong (Frontiers in Immunology, 2021)
Objective: To explore the role of the Nlrp3 inflammasome activation in the development of hemolytic uremic syndrome (HUS) induced by Stx2 and evaluate the efficacy of small molecule Nlrp3 inhibitors in preventing the HUS. Methods: Peritoneal macrophages (PMs) isolated from wild-type (WT) C57BL/6J mice and gene knockout mice (Nlrc4-/-, Aim2-/-, and Nlrp3-/-) were treated with Stx2 in vitro and their IL-1β releases were measured. WT mice and Nlrp3-/- mice were also treated with Stx2 in vivo by injection, and the biochemical indices (serum IL-1β, creatinine [CRE] and blood urea nitrogen [BUN]), renal injury, and animal survival were compared. To evaluate the effect of the Nlrp3 inhibitors in preventing HUS, WT mice were pretreated with different Nlrp3 inhibitors (MCC950, CY-09, Oridonin) before Stx2 treatment, and their biochemical indices and survival were compared with the WT mice without inhibitor pretreatment. Results: When PMs were stimulated by Stx2 in vitro, IL-1β release in Nlrp3-/- PMs was significantly lower compared to the other PMs. The Nlrp3-/- mice treated by Stx2 in vivo, showed lower levels of the biochemical indices, alleviated renal injuries, and increased survival rate. When the WT mice were pretreated with the Nlrp3 inhibitors, both the biochemical indices and survival were significantly improved compared to those without inhibitor pretreatment, with Oridonin being most potent. Conclusion: Nlrp3 inflammasome activation plays a vital role in the HUS development when mice are challenged by Stx2, and Oridonin is effective in preventing HUS.